Subjective financial scarcity today = objective financial scarcity in the future? The impact of subjective financial scarcity on saving for retirement - Pulk, Kristjan; Post, Thomas (Frontiers in Behavioral Economics, 2025)
Subjective financial scarcity poses a significant concern that negatively impacts individuals' wellbeing. With attention tunneling to present financial worries, individuals might neglect their future financial situation, even if they objectively have enough funds to save. Such behavior can contribute to a deficient financial situation in retirement. To assess the impact of subjective financial scarcity on the intention to save for retirement, we conduct an online vignette survey experiment (n = 134). Using the two-limit tobit model, we find that subjective financial scarcity leads to lower retirement savings rate. We contribute to the literature by testing theoretical predictions of scarcity theory, providing experimental evidence for the myopic financial behavior orientation of retirement saving rates. We offer practical implications for policymakers, suggesting that interventions that promote saving for retirement should be designed with subjective financial scarcity and stress reduction messages in mind.